Determining tipping points in aquatic ecosystems: The case of biodiversity and chlorophyll α relations in fish pond systems. (May 2015) - Vanacker, Marie; Wezel, Alexander; Payet, Vincent; Robin, Joël
Highlights: We compare different statistical methods and diversity indices to determine tipping points. We compare tipping points in different taxonomic groups. SEGMENTED and Jackknife first order are the most adequate method and diversity index to determine tipping points. Aquatic vascular plants are the best taxonomic group to respond to eutrophic changes. Abstract: The management of biodiversity in aquatic ecosystems requires knowing the state of water quality linked to regime shifts in various taxonomic groups. We examine this question by studying the fish ponds in the Dombes region, France. These waterbodies are characterized by a high diversity of species. High levels of nutrients due to certain fish farming practices may cause significant eutrophication leading to loss in biodiversity and a shift from high coverage of aquatic vegetation to phytoplankton dominance may also be observed. The aim of this study is to assess tipping points, thresholds for effect, along a gradient of chlorophyll α in different taxonomic groups: aquatic vascular plants, phytoplankton, dragonflies and aquatic macro-invertebrates. Tipping points are analyzed with three different statistical methods: a method which evaluates tipping points with a difference in the mean (TMEAN), a second method which evaluates tipping point by comparing the mean and linear regressions before and after the tipping point (FSTAT) and third a method which evaluates linear regressions with a pivotal tipping point (SEGMENTED). We also compare tipping points for the different taxonomic groups using five different diversity indices: Observed richness, Jackknife first order, Fisher's alpha, Simpson index and Evenness. Our results show that there is an important variation in tipping points following the three statistical methods, but the SEGMENTED is the best method for evaluating tipping points. We observe a high difference of tipping point values for the different taxonomic groups depending on the diversity indices used. Jackknife first order has a better performance to evaluate a eutrophic change according to the diversity than the other indices. In all taxonomic groups, aquatic vascular plants are the most impacted by the chlorophyll α and almost all their tipping points are observed around 60 μg/L chlorophyll α concentrations. No significant relationship is found between chlorophyll α and phytoplankton diversity, while the two other groups, dragonflies and macro-invertebrates, are both impacted by the chlorophyll α but their relevant tipping points are situated in higher values than aquatic vascular plants.